2014
DOI: 10.4236/psych.2014.53028
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Anger of Rural and Urban Adolescents

Abstract: The purpose of the present study was to investigate the relationship between stress and anger of rural and urban adolescents of Chittagong district in Bangladesh. The sample of the study consisted of 120 respondents of whom 60 were male (30 rural and 30 urban) and 60 were female (30 rural and 30 urban). Their age levels were 13 -19. They were selected purposively from different areas of Chittagong district in Bangladesh. Bengali version of Life Stress Scale (Fahim, 2001) was used to measure life stress and Ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…Given the excessive academic pressures of upcoming graduation examinations in higher grades and increasing family expectations for academic success, this finding is unsurprising. This study suggests that urban adolescents have higher odds of experiencing stress than rural adolescents, which is consistent with the findings of another study [ 32 ]. Recent findings suggest that urbanicity does not impact mental health directly, but it is associated with acute autonomic nervous system and hypothalamic-pituitary-adrenal axis reactivity.…”
Section: Discussionsupporting
confidence: 92%
“…Given the excessive academic pressures of upcoming graduation examinations in higher grades and increasing family expectations for academic success, this finding is unsurprising. This study suggests that urban adolescents have higher odds of experiencing stress than rural adolescents, which is consistent with the findings of another study [ 32 ]. Recent findings suggest that urbanicity does not impact mental health directly, but it is associated with acute autonomic nervous system and hypothalamic-pituitary-adrenal axis reactivity.…”
Section: Discussionsupporting
confidence: 92%
“…The authors' views are also supported by one of the studies which focus that counseling program should be provided to increase adolescents self-esteem at institutional as well as at home which will help to decrease symptoms related to their stress and depression. Authors explained that parents have to understand their children's expectations and demand, they should be very alert about selecting their peer groups also and should develop and sustain a strong and healthy emotional connection with their children (Dey et al, 2014).…”
Section: Discussion and Conclusion:-mentioning
confidence: 99%
“…The study shows that it is just because of the busy schedule of the parents and higher expectations due to societal pressure. So, the problem related to the competitive environment in the school, peer pressure, demands of parents, and teachers to get high grades to make the more stressful situation for urban adolescents (Dey et al, 2014). Due to these pressures, sometimes these adolescent leads to develop suicide tendency and hence every parent must be more careful in nurturing their child, especially during the adolescent period.…”
mentioning
confidence: 99%
“…Among non-clinical population, Cubito and Brandon (2000) found that adult women showed higher anger scores than adult men; nevertheless, some researchers have found no differences between men and women with regards to the feeling of anger, although women tend to express it more frequently (Averill, 1983;Evers, Fisher, Rodriguez-Mosquera, & Manstead, 2005). In the case of boys and girls, some studies have not found differences in the level of anger between both genders (Burt, 2014;Pullen et al, 2015), but other studies have found that female adolescents experienced a higher level of anger than male adolescents (Dey, Rahman, Bairagi, & Roy, 2014;Spielberger & Reheiser, 2009).…”
Section: Introductionmentioning
confidence: 99%